METHODOLOGICAL ASPECTS OF FORMATION OF SUBJECT AND COMMUNICATIVE COMPETENCIES OF FOREIGN STUDENTS WHEN LEARNING PHYSICS AT PREPARATORY DEPARTMENTS - Olexandr О. Kalenyk; Tetiana L. Tsaregradska; Inna V. Plyushchay (Alfred Nobel University Publisher, 2019)
The leading methodological direction of foreign students' training for higher education institutions is the introduction of a functional and semantic approach, one aspect of which is the formation of communicative-oriented competencies (subject-speech), which ensures the communication of students in the educational and professional field. In order to complete these tasks and construct a communicativeoriented model of learning, it is necessary to consider subject and speech competencies as integrated and interconnected concepts, to define their main structural components (motivational, cognitive, activity) and to specify their content when foreign students study Physics and Ukrainian language. The language and communicative readiness of students to professional communication in the study of special disciplines, in particular physics, is formed on the basis of the scientific style of language, which provides assimilation of language competences. The authors developed and methodologically substantiated the ways of implementing a two-dimensional approach to the formation of subject, linguistic competencies of foreign students in the study of Physics at the preparatory departments at higher educational institutions of Ukraine. Experience at the preparatory departments confirms that the effectiveness of pre-professional training of students depends on inter-subject coordination and the combination of professional and linguistic training. Only a complete list of compositional and content situations of the language of the specialty and structures of the scientific style of language will be able to reflect the real volume of knowledge on discipline. For the active implementation of these models, for the formation of linguistic competencies, it is necessary to develop a holistic system of exercises for the assimilation of each component of scientific knowledge, to consider the stages and the sequence of their inclusion in the educational process. Professional-oriented language teaching forms a sufficient and high level of formation of subject-linguistic competencies. An important aspect of the formation of physical competencies is the definition of criteria, indicators, and levels of their formation. Only if the language course is integrated with the course of Physics, it is possible to achieve a certain level of educational activity in accordance with the objectives of education. Further areas of improvement of the formation of subject-language competences of foreign students in the study of physics may be as follows: the definition of criteria and indicators of the formation of professionalsignificant knowledge and vocational-speaking competencies; сreation of Ukrainian-language textbooks for foreign students professionally oriented at natural sciences.